1977
DOI: 10.1177/1077727x7700500403
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences and Selected Socioeconomic Variables Related to Physical Adequacy of Housing

Abstract: To a large extent, the adequacy of physical conditions of housing is considered to be associated with the consumer's preferences for alternative consumption items and various socioeconomic characteristics of that consumer. The relationships of housing adequacy to race, town, tenure, wife's education, occupational prestige of the head of household, family income, and preferences for long‐ and short‐range alternatives to housing were analyzed to determine which socioeconomic conditions and preferences were relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Looking at empirical studies on adequate housing, Zey-Ferrell et al, (1977) examined the relationships between housing adequacy and the socio-economic and demographic characteristics of 361 females in two Louisiana communities in the US. That study found that housing was significantly less adequate for (i) blacks (ii) those living in the north Louisiana community (iii) renters (iv) families of females who possessed lower levels of education (v) males who worked at jobs with lower occupational prestige; and (vi) females who did not prefer to spend their resources on long-range alternatives to housing.…”
Section: Literature On Adequate Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at empirical studies on adequate housing, Zey-Ferrell et al, (1977) examined the relationships between housing adequacy and the socio-economic and demographic characteristics of 361 females in two Louisiana communities in the US. That study found that housing was significantly less adequate for (i) blacks (ii) those living in the north Louisiana community (iii) renters (iv) families of females who possessed lower levels of education (v) males who worked at jobs with lower occupational prestige; and (vi) females who did not prefer to spend their resources on long-range alternatives to housing.…”
Section: Literature On Adequate Housingmentioning
confidence: 99%
“…However, the studies by Morton et al, (2004) and Bonnefoy (2007) indicate that among these concepts, housing adequacy remains one of the least investigated. Zey-Ferrell et al, (1977) identified the adequacy of housing environment as having direct link with occupants' housing preferences and their socio-economic characteristics. Other studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, various studied have constructed housing index by using different housing facilities. See, for example, Hatch and Laura, (1998), Herrin et al, (2013), Nazli et al, (2003) and Zey-Ferrell et al, (1977) Herrin et al (2013) estimated the relationships between housing quality and occupant health using "count outcome" regression models consistent with the economic model and other empirical work, the results show that exposure to burning of biomass for cooking has the largest adverse health effect. Zainal et al, (2012) examined the relationship between housing conditions and the quality of life of the urban poor in Malaysia.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Crosby (1970) has examined the relationship between perceived levels of living and family welfare. Perceived normative housing deficits have been studied by Morris and Winter (1978), and consumer perceptions of housing adequacy have been researched by Zey-Ferrell, Kelley, and Bertrand (1977).…”
Section: Introductionmentioning
confidence: 99%